The Influence of Pocket Money and Profit Expectations on Mutual Fund Investment Interest - Haniv Amelia Oktaviani; Wuryaningsih Dwi Lestari (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the effect of pocket money and profit expectations on students’ interest in investing in money market mutual funds, with investment risk serving as a moderating variable. Methodology/approach: This research employs a quantitative approach using a survey method through questionnaires distributed to 100 active students of Universitas Muhammadiyah Surakarta. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. Results/findings: The findings reveal that pocket money has no significant effect on students’ interest in investing in money market mutual funds. Meanwhile, profit expectations and investment risk have a positive and significant influence on investment interest. However, investment risk does not moderate the relationship between pocket money or profit expectations and investment interest. These results indicate that perceived returns and risk awareness are the primary drivers of students’ investment intentions, rather than their personal financial capacity. Conclusion: Students’ investment behavior is shaped more by cognitive and perceptual factors than by financial availability. Limitations: This study is limited to one university and focuses on money market mutual funds, which may affect the generalizability of the findings. Contribution: The study contributes to the development of financial literacy among university students and provides insights for universities to design educational programs promoting safe, halal, and low-risk investment awareness for novice investors.